Processes of Discrimination and Humiliation Experienced by Ecuadorian Immigrant Workers in Spain - David Ortega‐Jiménez; Luis Alvarado; Alejandra Trillo; Francisco D. Bretones (Social Inclusion, 2023)
The workplace is currently one of the main places of discrimination for socially vulnerable groups such as immigrant workers, who are often required to take on highly stigmatized, menial jobs under supervisors who subject them to daily mistreatment and racism. This study adopted a qualitative approach to 42 semi‐structured interviews of Ecuadorian immigrant workers residing in Spain to explore the processes of discrimination these laborers feel in their everyday workplaces. The findings clearly indicate that immigrant workers can be victims of daily discrimination, which is evidenced by the higher degree of scrutiny and lower levels of trust they suffer compared to their Spanish counterparts, and by their supervisors’ lack of compliance with contractual agreements. As these immigrants are obliged to take on less qualified jobs, they suffer from a lack of recognition and a sense of being undervalued. This analysis also gathered evidence of interviewees’ daily humiliations imparted by their supervisors—and even, at times, by work colleagues—in the form of racial slurs, verbal abuse, and unequal treatment, leaving them feeling powerless and helpless. Most of our respondents in fact find themselves in a predicament they do not know how to confront and cannot reject. All of these factors lead to feelings of humiliation and lack of independence.